2001
DOI: 10.1375/1369052012803
|View full text |Cite
|
Sign up to set email alerts
|

Are Twins and Singletons Comparable? A Study of Disease-related and Lifestyle Characteristics in Adult Women

Abstract: The classic twin study is sometimes described as "the perfect natural experiment" for the investigation of the aetiology of complex disease, but assumptions of the twin design need to be empirically tested if their results are to be considered unbiased and representative of singleton populations. In this study comparisons of disease and prevalence of lifestyle characteristics have been made between twin participants in the St Thomas' Hospital UK adult twin registry, the largest twin volunteer register in the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
349
5
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 388 publications
(375 citation statements)
references
References 34 publications
19
349
5
2
Order By: Relevance
“…Selection bias is unlikely to be a problem because the study questionnaire did not focus on a particular disease and all the twin pairs recruited were unselected volunteers. Our twin population has also been found to be similar to a population-based singleton sample for a range of diseases including osteoporosis and osteoarthritis (21). No significant associations with risk factors were found.…”
Section: Discussionsupporting
confidence: 57%
“…Selection bias is unlikely to be a problem because the study questionnaire did not focus on a particular disease and all the twin pairs recruited were unselected volunteers. Our twin population has also been found to be similar to a population-based singleton sample for a range of diseases including osteoporosis and osteoarthritis (21). No significant associations with risk factors were found.…”
Section: Discussionsupporting
confidence: 57%
“…One of the studies is derived from a twin population, but the subjects from this cohort have been shown to be equivalent to the general UK population in terms of socioeconomic, lifestyle, anthropometric, and physiologic measures (31).…”
Section: Discussionmentioning
confidence: 99%
“…A further 2% ( n  = 102) did not attend a clinical session for BMD assessment, resulting in 3160 participants being included in the current analyses. This population has been shown to be representative of the general population in terms of BMD and dietary intake 22, 23…”
Section: Methodsmentioning
confidence: 99%